Enhancing Descriptive Writing Achievement of Tenth Graders by Using Internet Meme Picture - Rita Inderawati; Dea Ariani; Muslih Hambali (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2018)
ABSTRACTThe objectives of this study were to find out whether or not: (1) there was a significant difference in Descriptive Writing achievement after the tenth grade students of SMA Negeri 1 Indralaya Utara were taught by using internet meme picture and (2) there was a significant difference in Descriptive Writing achievement between the students who were taught by using internet meme pictures and those who were not. The samples of this study were X MIPA 1 and X MIPA 2 with the total number of 64 students. To collect the data, each group was given pre-test and post-test of writing. The data were analyzed by using Paired Sample t-test and Independent Sample t-test in SPSS version 22. The results from Paired Sample t-test showed that there was a significant difference in Descriptive Writing achievement before and after the tenth-grade students of SMA Negeri 1 Indralaya Utara were taught by using Internet Meme Picture. The result from Independent Sample t-test of the post-test in both experimental and control groups showed that there was a significant difference in Descriptive Writing achievement between the students who were taught by using Internet Meme Picture and those who were not as the r-value both of Paired Sample t-test and Independent Sample t-test results were lower than 0.05 (0.000 < .05). ABSTRAKTujuan penelitian ini adalah untuk mengetahui apakah: (1) ada perbedaan yang signifikan dalam menulis deskriptif setelah siswa kelas sepuluh SMA Negeri 1 Indralaya Utara diajarkan dengan menggunakan Internet Meme Picture dan (2) ada perbedaan yang signifikan dalam penulisan deskriptif antara siswa yang diajar dengan menggunakan Internet Meme Picture dengan mereka yang tidak. Sampel penelitian ini adalah kelas X MIPA 1 dan X MIPA 2 dengan jumlah total 64 siswa. Untuk mengumpulkan data, setiap kelompok diberikan pre-test dan post-test penulisan. Data dianalisis dengan menggunakan Paired Sample t-test dan Independent Sample t-test dengan SPSS versi 22. Hasil dari Paired Sample t-test menunjukkan bahwa ada perbedaan yang signifikan dalam penulisan deskriptif sebelum dan sesudah siswa kelas X SMA Negeri 1 Indralaya Utara diajarkan dengan menggunakan Internet Meme Picture. Hasil Independent Sample t-test dari post-test di kedua kelompok yaitu eksperimen dan kontrol menunjukkan bahwa ada perbedaan yang signifikan dalam prestasi penulisan deskriptif antara siswa yang diajar dengan menggunakan Internet Meme Picture dan dengan mereka yang tidak. Nilai kedua t-test yaitu hasil Paired Sample t-test dan hasil Independent t-test lebih rendah dari 0,05 (0,000 <0,05).How to Cite: Inderawati, R., Ariani, D. N., Hambali, M. (2018). Enhancing Descriptive Writing Achievement of Tenth Graders by Using Internet Meme Picture. IJEE (Indonesian Journal of English Education), 5(2), 176-190. doi:10.15408/ijee.v5i2.7666. Inserted: -